Young workers career success model: A psychological perspective on minimizing educated unemployment - Sumaryono, Sumaryono; A'yuninnissa, Rizqi Nur’aini; Dilla, Intan Fara; Aryana Pramestri, Zakiya Aryana Pramestri (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Young workers represent an important phenomenon in the current labour market, particularly due to a noticeable shift from organizationally based career choices toward professionally oriented career paths. This shift often leads to instability, as many young workers tend to leave unsuitable career paths or remain unemployed while waiting for opportunities that match their aspirations, a condition that may potentially increase unemployment and poverty rates.Purpose: This study aimed to identify the main psychological elements that contribute to career success among young workers.Method: The research was conducted in two phases. Study 1 employed qualitative interviews with four young workers to explore their subjective experiences of career success. Study 2 utilized a quantitative survey with 148 young worker respondents, applying descriptive and inferential analysis to validate the identified elements.Findings: The results revealed that career meaning plays the most dominant role in determining career success among young workers, followed by work–life balance and psychological safety. These findings highlight the salience of internal psychological factors rather than external conditions.Implication: The study suggests that fostering meaningful careers, promoting balance between personal and professional life, and ensuring psychological safety are essential strategies to enhance career success for young workers, with potential contributions to reducing unemployment and poverty levels among educated youth.